2015
DOI: 10.1088/1475-7516/2015/12/017
|View full text |Cite
|
Sign up to set email alerts
|

The non-linear power spectrum of the Lyman alpha forest

Abstract: Abstract. The Lyman alpha forest power spectrum has been measured on large scales by the BOSS survey in SDSS-III at z ∼ 2.3, has been shown to agree well with linear theory predictions, and has provided the first measurement of Baryon Acoustic Oscillations at this redshift. However, the power at small scales, affected by non-linearities, has not been well examined so far. We present results from a variety of hydrodynamic simulations to predict the redshift space non-linear power spectrum of the Lyα transmissio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
136
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 76 publications
(151 citation statements)
references
References 67 publications
14
136
1
Order By: Relevance
“…The simulations by Arinyo-i-Prats et al (2015) 9 find bF = −0.201 and βF = 1.205 (z = 3.0), and bF = −0.125 and βF = 1.364 (z = 2.5, interpolated). Numerical values are not reported for bF Γ, but by applying the integral form to the observed flux probability density functions (Kim et al 2007 , Table A3), we find bF Γ = 0.156 (z = 3.0) and 0.122 (z = 2.5).…”
Section: The Streaming Velocity Bias Coefficientmentioning
confidence: 95%
“…The simulations by Arinyo-i-Prats et al (2015) 9 find bF = −0.201 and βF = 1.205 (z = 3.0), and bF = −0.125 and βF = 1.364 (z = 2.5, interpolated). Numerical values are not reported for bF Γ, but by applying the integral form to the observed flux probability density functions (Kim et al 2007 , Table A3), we find bF Γ = 0.156 (z = 3.0) and 0.122 (z = 2.5).…”
Section: The Streaming Velocity Bias Coefficientmentioning
confidence: 95%
“…It can be chosen to be of one of the two forms given by Equation 21 of (McDonald 2003) or as presented in Arinyo-i-Prats et al (2015). Our standard fit uses the former.…”
Section: Model Of the Cross-correlationmentioning
confidence: 99%
“…There have been several studies in the past (e.g. [18,27,28]), that have shown that the Lyman-α forest is really measuring the amplitude of the linear matter power spectrum, the slope of the power spectrum, and possibly the effective running, all evaluated at a pivot scale of around 1-10 Mpc/h. Thus σ 8 and n eff used are good tracers of what is actually measured.…”
Section: Lyman-α Forest Constraintsmentioning
confidence: 99%